Rogue access point detection and tracking system using trilateration algorithm - Lee, Chiew Min; Ang, Boon Keat; Kok, Ser Leen; Ghali, Abdulrahman Aminu; Sabri, Nor ‘Afifah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
In the current digital era, network security is an essential concern, especially in the growing usage of wireless networks. Network security is vulnerable to rogue access points, and unauthorized wireless access points lead to security threats. The rapid growth of wireless technology has led to an increased demand for wireless networks in numerous sectors, including educational institutions. However, the widespread use of wireless networks has also introduced new security challenges, particularly the threat of rogue access points (RAPs). A rogue access point is an unauthorized wireless access point that has been installed on a network without the knowledge or approval of the network administrator. This project aims to evaluate and implement the most effective method for detecting RAPs in tertiary institutions. Besides, that the project introduces a robust method called trilateration algorithm. Therefore, the proposed trilateration algorithm if implemented will detect and reduce the risk of unauthorized network access in tertiary institutions and save the danger of financial loss. In addition, a preliminary study will be conducted to identify potential network security vulnerabilities and a literature review will be carried out to analyze the latest research on rogue access points to compare with our proposed trilateration algorithm. On this basis, the concept of mitigating the threat of rogue access point attacks using the proposed approach may be considered when designing a framework to mitigate the rogue access point in tertiary institutions.